2009
DOI: 10.1097/hp.0b013e3181ae8ab3
|View full text |Cite|
|
Sign up to set email alerts
|

Lauriston S. Taylor Lecture: Yucca Mountain Radiation Standards, Dose/Risk Assessments, Thinking Outside the Box, Evaluations, and Recommendations

Abstract: The Yucca Mountain high-level radioactive waste repository is designed to contain spent nuclear fuel and vitrified fission products. Due to the fact that it will be the first such facility constructed anywhere in the world, it has proved to be one in which multiple organizations, most prominently the U.S. Congress, are exercising a role. In addition to selecting a site for the facility, Congress specified that the U.S. Environmental Protection Agency (U.S. EPA) promulgate the associated Standards, the U.S. Nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These findings from Wilhite et al (1998) and especially from Zvonova (1989) greatly weakens the simplified argument discussed above; namely, 129 I has a long half-life, low biological half-life, and the body can take up only a limited mass of iodine in the presence of an omnipresent background of 127 I. Yet, this argument is often made (Rogers and Associates Engineering Company 1987; Bhattacharyya and Janati 1987;IAEA 1987;Soldat 1976;Kocher 1981;Kocher 1991;Moeller 2005;Cohen 1988). At issue, is that this relatively new finding by Zvonova (1989) demonstrated that at elevated iodine environments, the thyroid shrinks and the rate of uptake decreases, compromising our ability t o m ake linear extrapolations and assumptions regarding thyroid iodine uptake.…”
Section: Radioiodine Exposure and Dose To Humansmentioning
confidence: 97%
“…These findings from Wilhite et al (1998) and especially from Zvonova (1989) greatly weakens the simplified argument discussed above; namely, 129 I has a long half-life, low biological half-life, and the body can take up only a limited mass of iodine in the presence of an omnipresent background of 127 I. Yet, this argument is often made (Rogers and Associates Engineering Company 1987; Bhattacharyya and Janati 1987;IAEA 1987;Soldat 1976;Kocher 1981;Kocher 1991;Moeller 2005;Cohen 1988). At issue, is that this relatively new finding by Zvonova (1989) demonstrated that at elevated iodine environments, the thyroid shrinks and the rate of uptake decreases, compromising our ability t o m ake linear extrapolations and assumptions regarding thyroid iodine uptake.…”
Section: Radioiodine Exposure and Dose To Humansmentioning
confidence: 97%
“…There is ongoing discussion on the uncertainty of dose-torisk factors, caused by the difficulty of assessing health effects resulting from chronic radiation exposure (26,72). It has also been pointed out that health impacts might change in the not-too-distant future because of the expected progress in preventing and curing cancer (73).…”
Section: Safety Standards For Geologic Repositoriesmentioning
confidence: 99%